"Entre Nosotras:" a qualitative study of a peer-led PrEP project for transgender latinas - Sophia Zamudio-Haas; Kim Koester; Luz Venegas; Ariana Salinas; Cinthya Herrera; Luis Gutierrez-Mock; Layla Welborn; Madeline B. Deutsch; Jae Sevelius (BMC, 2023)
Abstract Background Uptake of HIV pre-exposure prophylaxis (PrEP) remains low among transgender people as compared to other subgroups, despite high rates of HIV acquisition. In California, Latinx people comprise 40% of the population and Latina transgender women experience some of the highest burden of HIV of any subgroup, indicating a critical need for appropriate services. With funding from the California HIV/AIDS Research Programs, this academic-community partnership developed, implemented, and evaluated a PrEP project that co-located HIV services with gender affirming care in a Federally Qualified Heath Center (FQHC). Trans and Latinx staff led intervention adaptation and activities. Methods This paper engages qualitative methods to describe how a PrEP demonstration project- Triunfo- successfully engaged Spanish-speaking transgender Latinas in services. We conducted 13 in-depth interviews with project participants and five interviews with providers and clinic staff. Interviews were conducted in Spanish or English. We conducted six months of ethnographic observation of intervention activities and recorded field notes. We conducted thematic analysis. Results Beneficial elements of the intervention centered around three intertwined themes: creating trusted space, providing comprehensive patient navigation, and offering social support "entre nosotras" ("between us women/girls"). The combination of these factors contributed to the intervention's success supporting participants to initiate and persist on PrEP, many of whom had previously never received healthcare. Participants shared past experiences with transphobia and concerns around discrimination in a healthcare setting. Developing trust proved foundational to making participants feel welcome and "en casa/ at home" in the healthcare setting, which began from the moment participants entered the clinic and continued throughout their interactions with staff and providers. A gender affirming, bilingual clinician and peer health educators (PHE) played a critical part in intervention development, participant recruitment, and patient navigation. Conclusions Our research adds nuance to the existing literature on peer support services and navigation by profiling the multifaced roles that PHE served for participants. PHE proved instrumental to empowering participants to overcome structural and other barriers to healthcare, successfully engaging a group who previously avoided healthcare in clinical settings.